KILLING THE CURE? Is targeting LIF to treat pancreatic cancer a dangerous case of mistaken identity? - Su Metcalfe (Elsevier, 2022)
Leukaemia Inhibitory Factor (LIF) is a stem cell growth factor critical to health. LIF belongs to the IL-6 family of cytokines but LIF-signalling is unique and qualified by its cell surface receptor, LIF-R. As a strategy to treat pancreatic cancer, Hunter et al. [1] report an engineered therapeutic LIF-Trap (soluble LIF-R) to deplete human LIF. Whilst applauding the engineering success of the LIF-Trap, I argue a case of mistaken identity. Is it LIF, or IL-6, promoting tumour progression? The rationale is based on the earlier work of the same group reported by Shi et al. [2] who have already generated a specific anti-LIF antibody for the same therapeutic purpose as the LIF-Trap: this antibody has since been acquired by a leading pharmaceutical company. CRITIQUE: There are two major issues with the Hunter and Shi publications. First Safety - Hunter claims safety of their LIF-Trap despite extensive data arguing to the contrary: thus removal of LIF signalling risks pathogenic effects in multiple systems. Second Scientific - the group fail to take into account LIF biology, where mode of action places IL-6, rather than LIF, as candidate for driver of tumour progression. Importantly, clinical data suggests LIF-signalling functions as a tumour suppressor in pancreatic cancer [3], raising the question - would removal of LIF-signalling be counter-indicated in cancer?